Central banking in a small open economy : policy evaluation and challenges - Boamah, Daniel ([Caribbean Centre for Money & Finance] {St. Augustine]TT, 2000)
Formulates and tests a policy evaluation model that is applicable to the characteristics of a small open economy with a fixed exchange rate.